2020
DOI: 10.7150/ijms.49253
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of volume-controlled, pressure-controlled, and pressure-controlled volume-guaranteed ventilation during robot-assisted laparoscopic gynecologic surgery in the Trendelenburg position

Abstract: Background: Pressure-controlled ventilation volume-guaranteed (PCV-VG) is being increasingly used for ventilation during general anesthesia. Carbon dioxide (CO2) pneumoperitoneum in the Trendelenburg position is routinely used during robot-assisted laparoscopic gynecologic surgery. Here, we hypothesized that PCV-VG would reduce peak inspiratory pressure (Ppeak), compared to volume-controlled ventilation (VCV) and pressure-controlled ventilation (PCV). Methods: In total, 60 patients were enrolled in this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…Of those, 351 had to be excluded, resulting in 21 publications that were full-text assessed for eligibility. Four publications had to be excluded, finally resulting in 17 studies that underwent the following qualitative evaluation [ 6 , 7 , 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A flow chart of the search strategy and study selection are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 351 had to be excluded, resulting in 21 publications that were full-text assessed for eligibility. Four publications had to be excluded, finally resulting in 17 studies that underwent the following qualitative evaluation [ 6 , 7 , 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A flow chart of the search strategy and study selection are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 3 Moreover, PCV-VG improves respiratory dynamics in robot-assisted laparoscopic gynecologic surgery with Trendelenburg position. 11 Importantly, PCV-VG decreases the release of norepinephrine, reduces the inflammatory response and lung injury, protects the lung function of elderly patients with one-lung ventilation in thoracotomy. 12 , 13 The above results provide a basis for the study of PCV-VG in pediatric laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of the DCV mode, such as the AutoFlow or PCV-VG (pressure-controlled ventilation volume guaranteed), has been reported to be useful in maintaining lower PAWP during laparoscopic surgeries requiring the Trendelenburg position, compared with VCV, where the patient is ventilated using tracheal intubation [ 5 , 6 ]. The advantage of DCV over PCV is that the former can maintain adequate tidal volume throughout the procedure, even if lung compliance is altered.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DCV has the advantages of both PCV and volume-controlled ventilation (VCV) and can, therefore, prevent PAWP elevation and ensure target tidal volume even when lung compliance changes, such as during laparoscopy and in the Trendelenburg position [ 5 ]. During laparoscopic surgery in the Trendelenburg position with tracheal intubation, DCV has been reported to result in lower PAW P values than VCV [ 5 , 6 ]. Thus, suppressing PAWP with AutoFlow ventilation may prevent airway leak during laparoscopic gynecological surgery with pLMA.…”
Section: Introductionmentioning
confidence: 99%